2023
DOI: 10.1177/03946320231185703
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating CD73 and adenosine deaminase are associated with disease severity in hospitalized patients with COVID-19

Abstract: Objective SARS-CoV-2 infection has been shown to result in increased circulating levels of adenosine triphosphate and adenosine diphosphate and decreased levels of adenosine, which has important anti-inflammatory activity. The goal of this pilot project was to assess the levels of soluble CD73 and soluble Adenosine Deaminase (ADA) in hospitalized patients with COVID-19 and determine if levels of these molecules are associated with disease severity. Methods Plasma from 28 PCR-confirmed hospitalized COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From another perspective, Rud et al [51] analyzed plasma from patients hospitalized with COVID-19 for the effects of infection on CD73 activity. As a result, they also found a reduction in the expression of these ectonucleotidases.…”
Section: The Interaction Of Sars-cov-2 On Purinergic Receptor Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…From another perspective, Rud et al [51] analyzed plasma from patients hospitalized with COVID-19 for the effects of infection on CD73 activity. As a result, they also found a reduction in the expression of these ectonucleotidases.…”
Section: The Interaction Of Sars-cov-2 On Purinergic Receptor Expressionmentioning
confidence: 99%
“…As a result, they also found a reduction in the expression of these ectonucleotidases. However, they suggested that reduced nucleotide hydrolysis leads to reduced Ado production, preventing its expression of anti-inflammatory activity [51]. Considering the indications from scientific data of the anti-inflammatory effects of the P1 receptor family, this lack of Ado can be seen as a mediator for reducing the anti-inflammatory and neuroprotective activity presented by these receptors [52].…”
Section: The Interaction Of Sars-cov-2 On Purinergic Receptor Expressionmentioning
confidence: 99%
See 1 more Smart Citation